Psychometric properties of the Malay version of the job satisfaction survey among Malaysian military personnel - Ang, Chin Siang; Abu Talib, Mansor; Juhari, Rumaya; Madon, Zainal (Universiti Putra Malaysia Press, 2014)
Job satisfaction is directly related to a number of positive outcomes at work and in certain other aspects of life. In the past few years, job satisfaction among the armed forces has received much attention, but the results of research have been contradictory, in view of the lack of psychometrically robust instrument. Due to its multidimensional orientation, Job Satisfaction Survey has been widely used to assess job satisfaction across different types of job. Although JSS is a promising measure, it has never been validated in the armed forces context. Thus, the aim of this study was to examine the psychometric properties of the Malay version of the Job Satisfaction Survey (Spector, 1965) using data from Malaysian military personnel . With this is mind, a group of male navy personnel from selected navy bases were recruited to be respondents. Through exploratory factor analyses (EFA), results yielded a five-subscale model with 28 items, namely: recognition, affection, fairness, expectation, and workload. In addition, the validity and stability of the five-dimensional structure of the scale were evident in this study using confirmatory factor analyses (CFA). In summary, this study confirmed the psychometric properties of the scale and can further be used to measure job satisfaction in the armed force setting.